2007
DOI: 10.1210/en.2007-0099
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Prevents Thyroid Hormone-Induced Cardiac Hypertrophy

Abstract: Thyroid hormones (THs) have many effects on the cardiovascular system including cardiac hypertrophy. Although THs induce cardiac hypertrophy, the mechanism through which they exert this effect is unknown. We previously found that THs activate signaling related to increased protein synthesis [mammalian target of rapamycin (mTOR) and p70 S6 kinase] in the heart. It is unknown whether this activation contributes to TH-induced hypertrophy or whether it is merely incidental. In this study, we used rapamycin to inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
75
2
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 19 publications
14
75
2
6
Order By: Relevance
“…Hypertrophic cells arrested in cell cycle undergo an increase in protein synthesis. 28,[37][38][39] Cell cycle progression is related to protein synthesis during cell proliferation. 40,41) Thus, cell cycle arrest can be accompanied by depressed protein synthesis in H 2 O 2 -treated H9c2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertrophic cells arrested in cell cycle undergo an increase in protein synthesis. 28,[37][38][39] Cell cycle progression is related to protein synthesis during cell proliferation. 40,41) Thus, cell cycle arrest can be accompanied by depressed protein synthesis in H 2 O 2 -treated H9c2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of Atg7 by Ad-Atg7-RNAi inhibits autophagy in rat neonatal cardiomyocytes and then induces cardiomyocyte hypertrophy with typical characteristics. 29 Rapamycin, a potent activator of autophagy, prevents cardiac hypertrophy induced by thyroid hormone treatment, 35 or aortic banding, 36 and regresses existing cardiac hypertrophy. 37 These suggest that a decrease in autophagy at the hypertrophied state facilitates cardiac hypertrophic response.…”
Section: Autophagy In Cardiac Hypertrophymentioning
confidence: 99%
“…For instance, Dammrich and Pfeifer observed that cardiac hypertrophy induced by aortic constriction led to inhibition of autophagy in cardiac myocytes undergoing hypertrophy and proposed that the inhibition of degradation was important in growing myocytes since autophagy-mediated protein degradation antagonizes cell growth [13]. Rapamycin, a potent activator of autophagy, was demonstrated to prevent cardiac hypertrophy induced by thyroid hormone treatment [48] or aortic banding [49]. McMullen et al found that rapamycin treatment was even able to regress already established cardiac hypertrophy induced by pressure overload and improve cardiac function [50].…”
Section: Autophagy In Ischemia and Reperfusionmentioning
confidence: 99%